Preparação e performance de obras para percussão e mediação tecnológica: questões e relações entre o percussionista e a eletrônica em tempo real - Bragança, Breno Gervásio (2017)
This research is divided in two parts: (1) Artistic Production and (2) Article. The first part presents the repertoire and programs notes of pieces chosen for two recitals needed for the conclusion of the research - the first on July fifteen, two thousand sixteen at seven p.m, and the second on March thirty-one, two thousand sixteen at twelve p.m - and other concerts and performances related to the research. The second part propose to approach issues related to the preparation and performance of pieces for percussion and technological mediation, with emphasis in the relationship between the percussionist and the live electronics, starting from preparation and performance of two chosen pieces, namely, `Vibraphone and Electronics' (2012), from Baljinder Sekhon and `SprachSchlag' (2000), from Hans Tutschku. Practical issues, both of relationship between percussionist and electronics as between the percussionist and the instrumental part will be addressed. We also discuss some conceptual issues of the performance, not only the referenced pieces per si, but the repertoire for percussion and live electronics raise. We conclude that the preparation and performance of the chosen works offered challenges regarding both instrumental performance and electronic mediation, but they provided interesting and valid aesthetic experiences and proved to be a response to the technology and society of our time. The historical parallels between the classical western percussion and electronic music, such as aesthetic interest and mutual important composers, jointly with the learning of new techniques and the handling of different instruments and objects present in the canonical repertoire of the percussion are of great value to the musician who works with the repertoire with electronics, which leaves the percussionist in a position of privilege, where some of the skills developed in his metier are also shared with the metier of electronic music.